Two step fractionation of oil palm empty fruit bunches integrating hydrothermal-organosolv pretreatment for enhanced lignin extraction and enzymatic hydrolysis efficiency - Ningsi Lick Sangadji; Candra Wijaya; Maktum Muharja; Elaine Elaine; Hanny Frans Sangian; Raymond Lau; Arief Widjaja (Case Studies in Chemical and Environmental Engineering)
Lignocellulosic biomass, consisting of cellulose, hemicellulose, and lignin, represents a sustainable alternative to fossil fuel resources. However, its full utilization remains unexplored, as many studies have focused on recovery only one or two components, often discharge the rest. This study aims to achieve total utilization of oil palm empty fruit bunch (OPEFB) through sequential hydrothermal-organosolv pretreatment. Hydrothermal pretreatment was first employed to extract hemicellulose, followed by organosolv pretreatment to recover lignin. The effects of temperature (175–200 °C) and solvent concentration (60–80 %) on organosolv pretreatment were evaluated focusing on lignin recovery and purity. Hydrothermal pretreatment statistically effective in enhancing lignin extraction during subsequent organosolv pretreatment resulting in increased lignin recovery and purity. The highest lignin recovery of 47.13 % with a purity of 82.95 % was obtained at 185oC and 80 % solvent concentration. Lignin characterization using FTIR, NMR, TGA, and SEM revealed structural and morphological changes induced by pretreatment steps. Subsequently, the solid residue from this process was further subjected to enzymatic hydrolysis. This resulted in a reducing sugar production of 10.21 g/L after 72 h, an improvement of more than threefold compared to solid residue from single step organosolv pretreatment. These findings highlight the efficiency of the combined pretreatment method, presenting a promising strategy for lignocellulosic biomass fractionation and biorefinery.